2023
DOI: 10.3390/antibiotics12071085
|View full text |Cite
|
Sign up to set email alerts
|

Isavuconazole Exposure in Critically Ill Patients Treated with Extracorporeal Membrane Oxygenation: Two Case Reports and a Narrative Literature Review

Abstract: Effective dosing of isavuconazole in patients supported by extracorporeal membrane oxygenation (ECMO) is important due to the role of isavuconazole as a first-line treatment in patients with influenza- and COVID-19-associated pulmonary aspergillosis. To date, robust pharmacokinetic data in patients supported by ECMO are limited. Therefore, it is unknown whether ECMO independently impacts isavuconazole exposure. We measured isavuconazole plasma concentrations in two patients supported by ECMO and estimated indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Recently, isavuconazole plasma concentration measurements in 7 critically ill patients with ECMO showed that isavuconazole was not altered by the ECMO oxygenator and that median plasma concentrations were >1 mg/L 24 hours after the first routine loading dose [ 25 ]. In 2 recently published cases, the 24-hour areas under the concentration–time curve and trough concentrations of isavuconazole were lower in both patients with ECMO in comparison with previously published data from non-ECMO patients [ 26 ]. Another case series including 9 critically ill patients with IFD and ECMO revealed that isavuconazole plasma levels were lower in patients receiving ECMO therapy compared with patients without ECMO [ 27 ].…”
Section: Antifungal Agentsmentioning
confidence: 57%
“…Recently, isavuconazole plasma concentration measurements in 7 critically ill patients with ECMO showed that isavuconazole was not altered by the ECMO oxygenator and that median plasma concentrations were >1 mg/L 24 hours after the first routine loading dose [ 25 ]. In 2 recently published cases, the 24-hour areas under the concentration–time curve and trough concentrations of isavuconazole were lower in both patients with ECMO in comparison with previously published data from non-ECMO patients [ 26 ]. Another case series including 9 critically ill patients with IFD and ECMO revealed that isavuconazole plasma levels were lower in patients receiving ECMO therapy compared with patients without ECMO [ 27 ].…”
Section: Antifungal Agentsmentioning
confidence: 57%
“…Nevertheless, extrapolating these conclusions to critically ill patient could be inaccurate. The limited number of studies on isavuconazole Pk in critical care patients has shown inconsistent results [12][13][14]. Impaired renal or hepatic function, continuous renal replacement therapy (CRRT) or extracorporeal membrane oxygenation (ECMO) make drug concentrations prediction di cult, and thus, TDM could be necessary in this population [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%